Determinan Nilai Perusahaan di Pasar Modal Indonesia: Systematic Literature Review - Sisi Maghfirah Rahmah Sembiring; Ningrum Trija Kesuma; Nurul Mizna Sukma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to systematically examine the factors affecting firm value in the Indonesian capital market, focusing on profitability, liquidity, firm size, and ownership structure. The method used is a Systematic Literature Review (SLR) based on PRISMA, analyzing articles published in reputable international journals indexed in Scopus and nationally accredited journals (at least Sinta 4) since 2022. The review process involves formulating research questions, literature search, article selection, and thematic synthesis. The findings indicate that profitability positively affects firm value, while liquidity has a contextual impact. Firm size can enhance market confidence but may also lead to inefficiencies, and ownership structure influences firm value through control mechanisms and corporate governance. These findings emphasize the need for a comprehensive approach to managing the factors affecting firm value in the Indonesian capital market.